Subharmonic centrifugal pendulum vibration absorbers allowing a rotational mobility. (1st September 2022) - Mahe, V.; Renault, A.; Grolet, A.; Mahe, H.; Thomas, O.
Abstract: Rotating machines are often subjected to fluctuating torques, leading to vibrations of the rotor and finally to premature fatigue and noise pollution. This work addresses a new design of centrifugal pendulum vibration absorbers (CPVAs), used to reduce the vibrations in an automotive transmission line. These passive devices, composed of several masses oscillating along a trajectory relative to the rotor, are here tuned at a subharmonic of the targeted harmonic torque frequency. Thanks to the inherent non-linearities, a CPVA with two masses oscillating in phase opposition is able to efficiently counteract the input torque, with particular features such as saturation phenomena. This work particularly extends previous works to a new class of CPVA, whose peculiarity is that masses admit a significant rotation motion relative to the rotor, thus adding the benefit of their rotatory inertia. Results on the system's subharmonic response and its stability are obtained thanks to an analytical perturbation method, and design guidelines are proposed. The validity of those results is also confirmed through comparisons with numerical solutions and the performance of this subharmonic system is compared to that of a classical CPVA tuned at the torque frequency. Highlights: The subharmonic response of a CPVA with rotating pendulums is analysed. The stability of the subharmonic response is assessed analytically. Design guidelines are proposed to increase the performance of the CPVA. The analytical results are compared with numerical ones.